1998
DOI: 10.1242/dev.125.6.1017
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin regulates the relative proportions of endocrine versus exocrine tissue during pancreatic development

Abstract: In this study, we have investigated the role of the embryonic mesenchyme in the development of the pancreas. We have compared the development in vitro of E12.5 rat pancreatic rudiments grown in the presence or absence of mesenchyme. When the E12.5 pancreatic epithelial rudiment is cultured in the presence of its surrounding mesenchyme, both morphogenesis and cytodifferentiation of the exocrine component of the pancreas are completely achieved, while only a few immature endocrine cells develop. The pancreatic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This is notably the case for the canonical WNT pathway, which controls acinar and progenitor proliferation from E12.5 (Baumgartner, Cash, Hansen, Ostler, & Murtaugh, 2014;Heiser, Lau, Taketo, Herrera, & Hebrok, 2006;Heller et al, 2002) and for Activin, which was shown to impact proliferation and branching in several organs, including the pancreas (Ritvos et al, 1995). Though Activin is expressed in the mesenchyme and epithelium, Follistatin, its antagonist, appears strictly mesenchymal (Miralles, Czernichow, & Scharfmann, 1998;Ritvos et al, 1995;Zhang et al, 2004). This is also the case for EGFR, which controls both epithelial proliferation and the early establishment of apico-basal polarity, which is expected to impact branching (L€ of-€ Ohlin et al, 2017;Miettinen et al, 2000).…”
Section: Mesenchymementioning
confidence: 96%
“…This is notably the case for the canonical WNT pathway, which controls acinar and progenitor proliferation from E12.5 (Baumgartner, Cash, Hansen, Ostler, & Murtaugh, 2014;Heiser, Lau, Taketo, Herrera, & Hebrok, 2006;Heller et al, 2002) and for Activin, which was shown to impact proliferation and branching in several organs, including the pancreas (Ritvos et al, 1995). Though Activin is expressed in the mesenchyme and epithelium, Follistatin, its antagonist, appears strictly mesenchymal (Miralles, Czernichow, & Scharfmann, 1998;Ritvos et al, 1995;Zhang et al, 2004). This is also the case for EGFR, which controls both epithelial proliferation and the early establishment of apico-basal polarity, which is expected to impact branching (L€ of-€ Ohlin et al, 2017;Miettinen et al, 2000).…”
Section: Mesenchymementioning
confidence: 96%
“…In pancreas, the microenvironment provides mechanical and chemical cues that are indispensable for the initial fate commitment, developmental growth, spatial organization and functional maturation of endocrine and exocrine cells 21 24 . Multiple signaling pathways controlling pancreatic epithelium development regulated by microenvironment-released factors were identified, including FGFR2, retinoic acid, BMP, TGFβ, Notch, Hedgehog and canonical Wnt pathways 25 34 . This knowledge has been adapted for human β-cell in vitro differentiation, enabling great advancements in pancreatic cell derivation.…”
Section: Introductionmentioning
confidence: 99%
“…In Madin Darby Canine Kidney (MDCK) cells, follistatin produced in the mesenchymal cells promotes tubulogenesis by inhibiting the action of activin A (Kojima, Maeshima, & Zhang, 2001). A similar function of the follistatin was also observed in the pancreas (Miralles, Czernichow, & Scharfmann, 1998). These results confirm that there is the interplay between activin and follistatin which help in the epithelial tubule morphogenesis and based on these we can postulate that a similar system is likely involved in the uterus/shell gland of the laying hen at around 20 hr p.o.…”
Section: Expression Of Inha Inhbb Inhba Acvr2a and Acvr2b In The Ovid...mentioning
confidence: 73%